Assessing the Effect of Leadership Styles on Employee Engagement: A Case Study of Construction Companies in Bhaktapur District - Pandey, Kul Prasad; Maharjan, Matina; Lamsal, Anisha (Nepalese Journal of Business and Management Studies, 2023)
The effect of leadership styles on employee engagement is widely recognized as an indispensable factor in organizational success. While previous studies have explored the relationships between leadership styles and employee engagement in different contexts, no research has yet scrutinized how leadership styles influence employee engagement specifically in construction companies within Bhaktapur. Thus, this study investigates the influences of various dimensions of leadership styles, such as transformational, transactional and laissez-faire leadership styles, on employee engagement in construction companies. This study utilized a quantitative research approach to analyse the effect of leadership styles on employee engagement. A combination of research designs, including descriptive, relational and causal research designs, was employed in the study. Relevant information was collected through a questionnaire from 137 samples, and the sampling method used in this study was convenient. The study indicates that an employee’s level of engagement with work is strongly influenced by leadership style. The results of the analysis show that transformational and transactional leadership styles have a positive but insignificant effect on employee engagement. Similarly, the laissez-faire leadership style positively and significantly affects employee engagement.